Rituximab/bendamustine/cytarabine for transplant‐eligible patients with mantle cell lymphoma: A retrospective study - Yuki Shimizu; Daisuke Kaji; Otoya Watanabe; Kyosuke Yamaguchi; Kosei Kageyama; Yuki Taya; Aya Nishida; Kazuya Ishiwata; Shinsuke Takagi; Hisashi Yamamoto; Yuki‐Asano Mori; Atsushi Wake; et al. (Cancer Medicine, 2023)
Abstract Background Mantle cell lymphoma is considered an aggressive B‐cell lymphoma. The optimal induction regimen remains controversial as no randomized controlled trial has compared the efficacy of different induction therapies. Method Herein, we performed a retrospective analysis of the clinical characteristics of 10 patients who received induction treatment consisting of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R‐CHOP) and rituximab, bendamustine, and cytarabine (R‐BAC) at Toranomon Hospital between November 2016 and February 2022. Result Although one patient discontinued R‐BAC therapy due to a rash, the other nine completed the scheduled chemotherapy. All patients achieved complete response, underwent high‐dose chemotherapy and autologous stem cell transplantation, and maintained complete remission with a median follow‐up of 15 months. Hematological adverse events (AEs) occurred in all patients; however, none developed documented infection. There were also no fatal non‐hematological AEs specific to R‐BAC. Conclusion R‐CHOP/R‐BAC may be a good induction therapy for transplant‐eligible patients with mantle cell lymphoma.